Gender differences in the association between self-rated health and hypertension in a Korean adult population - Shin Hee-Young; Shin Min-Ho; Rhee Jung-Ae (BMC, 2012)
Abstract Background Self-rated health (SRH) has been reported as a predictor of mortality in previous studies. This study aimed to examine whether SRH is independently associated with hypertension and if there is a gender difference in this association. Methods 16,956 community dwelling adults aged 20 and over within a defined geographic area participated in this study. Data on SRH, socio-demographic factors (age, gender, marital status, education) and health behaviors (smoking status, alcohol consumption, physical activity) were collected. Body mass index and blood pressure were measured. Logistic regression models were used to determine a relationship between SRH and hypertension. Results 32.5% of the participants were found to have hypertension. Women were more likely than men to rate their SRH as poor (p < 0.001), and the older age groups rated their SRH more negatively in both men and women (p < 0.001). While the multivariate-adjusted odds ratio (OR, 95% CI) of participants rating their SRH as very poor for hypertension in men was OR 1.70 (1.13-2.58), that in women was OR 2.83 (1.80-4.44). Interaction between SRH and gender was significant (p < 0.001). Conclusions SRH was independently associated with hypertension in a Korean adult population. This association was modified by gender.